Green Infrastructure, Climate Change and Spatial Planning: Learning Lessons Across Borders - André Samora-Arvela; João Ferrão; Jorge Ferreira; Thomas Panagopoulos; Eric Vaz (Journal of Spatial and Organizational Dynamics, 2017)
Climate change will further induce a generalized rise in temperature, heat waves, exacerbation of heat island effect, alteration of the precipitation regime variability with higher occurrence of high precipitation and flood events, reduction of quantity and quality of freshwater resources, disruption of agricultural production, leading to food security risk, degradation of recreational and aesthetic amenities, and loss of biodiversity. On other hand, Green Infrastructure, that is, the network of natural and semi-natural spaces within and around urban spaces, brings a constructive and protecting element that may mitigate and adapt to the local level impacts of climate change, strengthening local resilience. This paper presents a comparative study of various green infrastructures’ implementation based on analytics in the United States of America, United Kingdom and Portugal, and focuses on the degree of its alignment with the public policies of mitigation and adaptation to the impacts of climate change. Pursuant to the identification of successes and failures, this paper infers common strategies, goals and benchmarking on outcomes for more adequate decision implementation and sustainable spatial planning, considering the importance of green infrastructure.